2007
DOI: 10.1007/s11096-005-5975-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance and pharmacoepidemiology of drugs in a Mexican pediatric hospital. A proposed guide

Abstract: We describe the procedures of pharmacovigilance (PV) and pharmacoepidemiology (PE) of drugs in a pediatric hospital. These activities contribute to the detection and registration of adverse drug reactions and to determine the patterns of drug prescription among children attended at the hospital. The PV activities show that there is a relation between an increase in incidence of adverse drug reactions and the prescription of a larger number of drugs. The PE activities reveal that antibiotics are the most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…14 In a study the effect of food consistency on the pharmacokinetics of ranitidine in healthy volunteers the maximum plasma concentration (C max ) by food with solid consistency was found to be 665.81 ± 192.21 ng/ml and with food of liquid consistency the value was 1177.30 ± 588.19 ng/ml. 15 In another study of plasma pharmacokinetics of ranitidine HCl in foals the maximum plasma concentrations (C max ) was found to be 635.7 ng/ml. 16 In this study maximum plasma concentrations (C max ) for formulation 1 was found to range from 2.39-5.75 µg/ml with mean 4.63 ± 0.47µg/ml and for the formulation 2 maximum plasma concentrations (C max ) were ranging from 2.42-7.83 µg/ml with the mean value 4.76 ± 1.02 µg/ml.…”
Section: In-vivo Evaluationmentioning
confidence: 98%
See 1 more Smart Citation
“…14 In a study the effect of food consistency on the pharmacokinetics of ranitidine in healthy volunteers the maximum plasma concentration (C max ) by food with solid consistency was found to be 665.81 ± 192.21 ng/ml and with food of liquid consistency the value was 1177.30 ± 588.19 ng/ml. 15 In another study of plasma pharmacokinetics of ranitidine HCl in foals the maximum plasma concentrations (C max ) was found to be 635.7 ng/ml. 16 In this study maximum plasma concentrations (C max ) for formulation 1 was found to range from 2.39-5.75 µg/ml with mean 4.63 ± 0.47µg/ml and for the formulation 2 maximum plasma concentrations (C max ) were ranging from 2.42-7.83 µg/ml with the mean value 4.76 ± 1.02 µg/ml.…”
Section: In-vivo Evaluationmentioning
confidence: 98%
“…In a previous study the effect of food consistency on the pharmacokinetics of ranitidine in healthy volunteers, the volume of distribution by food with solid consistency was found to be 5.93 ± 1.69 L/Kg and with food of liquid consistency this value was 3.76 ± 0.61 L/Kg. 15 In another study of plasma pharmacokinetics of ranitidine HCl in foals the volume of distribution (Vd) was found to be 1.46 L/Kg. 16 In this study the volume of distribution (Vd) for formulation 1 ranged 0.010-0.025 L/Kg with mean 0.017 ± 0.005 L/Kg and for the formulation 2 it ranged 0.010-0.037 L/Kg with mean 0.019 ± 0.0088 L/Kg.…”
Section: In-vivo Evaluationmentioning
confidence: 99%
“…This is important because the most effective therapeutic range of many drugs, far from unnecessarily high concentrations with potential risk of producing toxicity in those taking them, is still unknown. 8…”
Section: Pharmacological Treatment Of Childrenmentioning
confidence: 99%
“…Another example of active surveillance comes in the form of monitoring patients during their stay in hospital. Hospital monitoring of adverse reactions in patients undergoing treatment were reported in Germany, Mexico and India (Kapp et al 1991, Juarez & Olguin 2007and Khairnar & Gade 2011. Hospital monitoring schemes involved; increasing awareness of both doctors and patients about Pharmacovigilance and potential adverse reactions, and improving methods for validation of adverse events (Kapp et al 1991), such as better expert review systems for reviewing adverse reaction reports.…”
mentioning
confidence: 99%
“…This led to improved quality and quantity of adverse event reports (Khairnar & Gade 2011). However, often these results were short-term only (Khairnar & Gade 2011) with further investment and incentives needed to encourage better reporting from the healthcare professionals in the future (Juarez &Olguin 2007 andKhairnar &Gade 2011).…”
mentioning
confidence: 99%